Proceedings of the National Tax Conference 2004 : gaining a competitive edge - National Tax Conference 2004 (2004 : Selangor); Lembaga Hasil Dalam Negeri Malaysia; Institut Percukaian Malaysia (Kuala Lumpur : Institut Percukaian Malaysia, 2004)
36